THE INFLUENCE OF ANXIETY AND DEPRESSIVE CONDITIONS ON AFTERINFARCTION REMODELING IN PATIENTS WITH STEMI - Petyunina, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Depression after AMI increases the frequency of re-hospitalization because of acute coronary syndrome, heart failure, MI, and is a risk factor for cardiac arrest and death. The objective of the study was to define the influence of anxiety-depressive disorders (ADD) on afterinfarction remodeling and the participation of sST2 fibrosis factor in this process. 100 STEMI patients were enrolled to the study, 81 (81 %) male and 29 (29 %) female, of average age of 58,94 ± 10,16 years. Examinations were performed twice: during 1–3 days after PCI with infarct-related artery stenting and included clinical-anamnesis data, blood analyses. The sST2 level was defined by immune-fermentative method with usage of «Presage ST2 Assay», Critical Diagnostics, USA. For ADD objectivization, HADS (Heart Anxiety and Depression Scale) and Teylor questionary were used. In 6 month 6-minute walk test and the volume fraction of interstitial collagen (VFIC) were done. Conclusion: ADD in patients with STEMI aggravates the course of postinfarction period and entails the progression of fibrotic-hypertrophic processes and corresponding remodeling of myocardium, decrease of physical tolerance.